An integrated assessment of Lithuanian economic sectors based on financial ratios and fuzzy MCDM methods - Baležentis, Alvydas; Baležentis, Tomas; Misiūnas, Algimantas (Technological and Economic Development of Economy, 2012)
The aim of this study was to offer a novel procedure for integrated assessment and comparison of Lithuanian economic sectors on the basis of financial ratios and fuzzy MCDM methods. The complex of interrelated issues regarding integrated assessment of economic sectors is discussed in the paper. The object of research is financial indicators of different Lithuanian economic sectors. The proposed procedure for multi-criteria comparison of economic sectors encompasses: 1) the indicator system, 2) application of fuzzy MCDM methods, and 3) inter-sectoral comparison based on ranks provided by fuzzy MCDM methods. The research covers period of 2007–2010, starting at the very beginning of the economic recession and, hopefully, ending with the upcoming recovery. The application of the three MCDM methods was successful. The results suggested the best performing sector being that of forestry and logging. Furthermore, enterprises operating in trade sector, hospitality sector, mining and quarrying sector, information sector, or manufacturing sector can be considered as working more efficiently than an average Lithuanian enterprise. At the other end of spectrum, construction, real estate, and transportation sectors were those severely damaged by the economic crisis: they were ranked below the average alternative. Meanwhile, relatively low positions of utilities sectors may be caused by their specifics. Finally, the transport sector can be considered as the typical victim of economic downturn.